Pemisahan Hasil Cair Pirolisis Sampah Plastik Pembungkus dengan Distilasi Batch - Siti Salamah; Agus Aktawan (CHEMICA: Jurnal Teknik Kimia, 2016)
Plastics waste has become a major issue for environment. Since it invented in 1907 plastic has become most used component on our daily lives. Plastic has many adavantages compared to other materials. In general plastic has a low density, light, varying strength and low manufacturing cost. However, plastic cannot degraded naturally and when not used anymore it will pollute the enviroment. One of method to degrade plastic is pyrolysis. In this method plastic will degrade to hydrocarbon which can used as liquid fuel. Pyrolysis of plastic occurs at high temperature of about 400 oC under free oxygen environment and produces small moleculer weight molecules. This research was conducted to determine the composition products of pyrolysis selective plastic at 450 oC in previous research. The method which used to separate products of pyrolysis is distillation with temperature between 50 oC to 240 oC to obtain liquid fuel as products of pyrolysis plastic. The results of this research were the distillate at 170 oC, 190 oC, 200 oC, 210 oC, 220 oC and 240 oC with volume 2 mL, 4,7 mL, 2,3 mL, 2,5 mL, 5,0 mL and 4,9 mL. And the most products component of pyrolysis plastic in previous research was obtain at 190 oC, 220 oC and 240 oC.